PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA CBR150R DI CIBINONG - Adyas, Dasmansyah; Setiawan, Ifan (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2019)
This study aims to determine the effect of product quality, price and brand image on purchasing decisions of Honda CBR150R motorcycles in Cibinong. The number of samples used is 100 people using the formula Sugiyono (2013: 220). Test Results t product quality and price have a positive. Whereas the brand brand image partially does not have a effect on the purchase decision variable of the Honda CBR150R motorcycle in Cibinong. Test results of product quality, price and brand image simultaneously have a positive and significant effect on the variable purchase decision for Honda CBR150R motorcycles in Cibinong. The results of the analysis of determination correlation (R Square) amounted to 0.545 This means that purchasing decisions are influenced by product quality, price and brand image of 54.5% and the remaining 55.5% is influenced by other factors not included in this study.